Rivaroxaban and apixaban in orthopaedics: is there a difference in their plasma concentrations and anticoagulant effects?. Issue 8 (December 2015) - Freyburger, Geneviève; Macouillard, Gérard; Khennoufa, Karim; Labrouche, Sylvie; Molimard, Mathieu; Sztark, François
Abstract : The aim of this study was to improve knowledge of what happens in the coagulation of orthopaedic patients under rivaroxaban and apixaban, in order to finalize and cross-validate effective measurement methods and to provide arguments for helping to reference one or the other drug in our central pharmacy. One hundred and two patients undergoing total hip or knee replacement were included. Half of them received rivaroxaban and the other half received apixaban. Blood samples ( n  = 244 with each drug) were taken at C max preoperatively and twice a week, apart from the day of the patient's discharge, when C trough concentration was targeted. Routine coagulation parameters, and functional and liquid chromatography tandem mass spectrometry assays for measurement of circulating concentrations were studied. The LC-MS/MS assay and the functional assays carried out in patients under routine conditions were highly correlated, apart from low concentrations (<30 ng/ml), which were affected by the variable individual potential to inhibit the exogenous bovine Xa used in the functional assays. After 1 week of treatment, the drugs differed: C max and C trough were closer when apixaban was taken twice daily (83 ± 39 and 58 ± 17 ng/ml) than with rivaroxaban taken once a day (113 ± 67 and 13 ± 20 ng/ml). Rivaroxaban had a greater influence on routine coagulation tests and reduced the maximum thrombin concentration more efficiently, as assessed by the thrombin generation test. Although rivaroxaban and apixaban present apparently similar constant rates, they exhibit significant differences in their concentrations and anticoagulant effects when studied ex vivo in orthopedic patients.